Self-monitoring of blood glucose: Use, frequency drivers, and cost in Argentina - Elgart, Jorge Federico (2014)
Background: Although test strips for self-monitoring of blood glucose (SMBG) represent around 50% of diabetes treatment cost in Argentina, little is known about their current use and relationship with different types of treatment. We therefore aimed to estimate the current use of test strips and identify the major use drivers and the percentage they represent of total prescription costs in 2 entities of the social security system (SSS) of Argentina. Methods: Observational retrospective study measuring test strip prescriptions delivered by pharmacies from the province of Buenos Aires (8115 records collected during 3 months provided by the Colegio de Farmacéuticos de la Provincia de Buenos Aires) of affiliates with type 2 diabetes (T2DM) from 2 large entities of the SSS system. Results: The average monthly test strips/patient used for SMBG was 97.5 ± 70.1. This number varied according to treatment: monotherapy with oral antidiabetic drugs (OAD) < combined OAD therapy < insulin treatment. Test strips represented a higher percentage of the total prescription cost in people under OAD monotherapy (84.6%) and lower in those with insulin analogs (46.9%). Conclusions: In our population, the type of hyperglycemia treatment was the main driver of test strip use for SMBG and its impact on the total prescription cost depends on the kind of such treatment. Since it has been shown that patients' education and prescription audit can optimize test strip use and treatment outcomes, implementation of such strategies could appropriately support, optimize, and reduce ineffective test strip use in people with T2DM.